EFFECT OF INFORMATION CLARITY ON WAITING TIME AND SERVICE QUALITY ON PATIENT SATISFACTION IN JKN OUTPATIENT PHARMACY UNIT AT DR. SAIFUL ANWAR HOSPITAL CY SERVICE UNIT OF JKN DR. SAIFUL ANWAR HOSPITAL - Wulandari, Meidina; Hariyanti, Tita; Ratri, Devita Rahmani (Journal of Community Health and Preventive Medicine, 2025)
Waiting time is one of the minimum standards in hospital pharmaceutical services. The waiting time for prescription services is measured as the interval between the submission of a prescription and the receipt of medication, which should be ≤30 minutes for non-compounded drugs and ≤60 minutes for compounded drugs. Timely service is closely related to customer satisfaction. However, prolonged waiting time for drug services still occurs at Dr. Saiful Anwar Hospital. Based on the 2023 community satisfaction index data, the score for the pharmaceutical installation was 83.88, and the lowest element was punctuality. Service quality is closely related to customer satisfaction, which is influenced by the clarity of information and services according to patients’ needs and expectations. The purpose of this study was to analyze the effect of information clarity on the length of waiting time for drug services and service quality on patient satisfaction in the JKN Outpatient Pharmacy Service Unit of Dr. Saiful Anwar Hospital. This study used a quantitative method with a cross-sectional approach. Samples were collected using consecutive sampling techniques with a total of 113 patients who accessed drug services at the JKN Outpatient pharmacy unit. The results showed that waiting time, tangibles, assurance, and empathy had a positive and significant effect on patient satisfaction. Reliability and responsiveness had a positive but not statistically significant on patient satisfaction. Among the variables, empathy had the strongest influence on satisfaction. Due to the dominant factor of empathy, it is recommended that Dr. Saiful Anwar Hospital improve its pharmaceutical services by providing training for pharmacists to deliver better and more empathetic service